Cover crops lower the dispersal of grapevine foliar pathogens from the ground and contribute to early-season disease management - Hasanaliyeva, Gultekin; Furiosi, Margherita; Rossi, Vittorio; Caffi, Tito (Frontiers in Plant Science, 2024)
Currently, fungicides are widely used to control grapevine foliar diseases. This study explored the possibility of decreasing the use of fungicides to control these diseases using cover crops in the interrow of vineyards. In small-scale experiments, we found that cover crops (namely horseradish Armoracia rusticana) were able to (i) reduce the numbers of airborne conidia of Botrytis cinerea (originating from an inoculum source above the soil) escaping the cover canopy by >85% with respect to the base soil and (ii) reduce the number of raindrops impacting the soil by 46%-74%, depending on the cover crop height and rain-originated splash droplets that escaped from the ground by 75%-95%, which reduced splash-borne inoculum. In two organic vineyards, for 2 years, fall-(mixture of Lolium perenne, Onobrychis viciifolia, and Trifolium repens) or spring-sown (a mixture of Vicia sativa and Sinapis sp.) cover crops could significantly delay (by 14-30 days) and reduce (till >90%) the development of downy and powdery mildew epidemics. This effect was more evident in plots untreated with fungicides than in treated plots. Cover crops also delayed the onset of epidemics depending on the type of cover crop and disease. Cover crops did not negatively affect grape yield and quality. Overall, the results showed that the introduction of cover crops in vineyard management can significantly contribute to disease control by lowering the load from ground to grapevine canopies of pathogen inocula, delaying disease onset, and reducing diseases severity during the season.